2016
DOI: 10.1097/jom.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Are Hospital Workers Healthy?

Abstract: Understanding the risk profile of hospital workers is critical to developing effective interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…Certain work settings such as health care are associated with higher prevalence of obesity due to work-related factors such as long work hours (>40 hours/week), shift work, and work-related stress (Luckhaupt, Cohen, Li, & Calvert, 2014; Sharma et al, 2016; Taylor & Bithoney, 2012). Compared with other U.S. workforces, hospital employees face higher cardiovascular risk factors have lower preventive health screening rates, lower participation in wellness programs, and higher emergency room (ER) and inpatient utilization rates (Sharma et al, 2016; Taylor & Bithoney, 2012). Moreover, health care employers are spending more on health care–related costs than employers from other industries (Taylor & Bithoney, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Certain work settings such as health care are associated with higher prevalence of obesity due to work-related factors such as long work hours (>40 hours/week), shift work, and work-related stress (Luckhaupt, Cohen, Li, & Calvert, 2014; Sharma et al, 2016; Taylor & Bithoney, 2012). Compared with other U.S. workforces, hospital employees face higher cardiovascular risk factors have lower preventive health screening rates, lower participation in wellness programs, and higher emergency room (ER) and inpatient utilization rates (Sharma et al, 2016; Taylor & Bithoney, 2012). Moreover, health care employers are spending more on health care–related costs than employers from other industries (Taylor & Bithoney, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In Western countries, there is a higher prevalence of hospital personnel with overweight and obese. A UK survey showed that approximately half of the NHS staff were overweight or obese 30. A study in Mexico revealed that the prevalence of personnel with overweight and obese was 60% 23.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital employees with obesity have shown higher consumption of potatoes, fats, sugary beverages, and spend more time watching television, playing computer games, and sitting 31. In a UK NHS staff survey, there was low compliance to a five-a-day fruits and vegetables recommendation and physical activity guidelines 30…”
Section: Discussionmentioning
confidence: 99%
“…Considering the frequent use of staff canteens [2,3,4] and the high prevalence of obesity and associated metabolic complications among health professionals [13,14,15,16], the nutritional quality of food served in hospital staff canteens is an important issue. Previous studies have often reported that frequent consumption of food produced outside the home, which is characterized by poor nutritional quality, is associated with adverse health outcomes [1].…”
Section: Discussionmentioning
confidence: 99%
“…In the UK around 61% of nurses and 49% of other healthcare professionals are either obese or overweight [14]. This high prevalence of obesity and associated metabolic complications among people working in the healthcare sector has also been observed in other countries [13,15,16]. Beyond the health risks of being overweight or obes for healthcare staff themselves, this may actually have clinical implications for patient care, as it has been found that lifestyle advice on diet and exercise given by an overweight healthcare professional may be less convincing to patients [13].…”
Section: Introductionmentioning
confidence: 95%